2010
DOI: 10.1007/s12566-010-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

Analytical potential of gold nanoparticles in functional aptamer-based biosensors

Abstract: Gold nanoparticles (AuNPs) exhibit many predominant capabilities such as high biocompatibility, chemical stability, strong localized surface plasmon resonance absorption, and high extinction coefficient in the visible region. These properties have enabled the extensive use of AuNPs in optical and electrochemical biosensors. As a kind of functional nucleic acids, aptamers can be considered as a valid alternative to antibodies or other bio-receptors and have been widely employed to develop novel biosensors. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 170 publications
0
8
0
Order By: Relevance
“…In addition, the conjugation of aptamers on AuNPs has also been well accomplished [28,30,31,32]. The electrochemical signal enhancement of the sensor using AuNPs can be classified into two approaches [33]. First, AuNPs are utilized as a label for signal amplification.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the conjugation of aptamers on AuNPs has also been well accomplished [28,30,31,32]. The electrochemical signal enhancement of the sensor using AuNPs can be classified into two approaches [33]. First, AuNPs are utilized as a label for signal amplification.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In comparison to antibodies, aptamers are cheaper, easier to synthesize and highly stable. [6][7][8][9] Over the past decade, molecular functional aptamers and the integration of aptamers into nanomaterials has become a new interdisciplinary field that aims at providing new hybrid systems for sensors, cancer cell targeting and therapy. 8,[10][11][12][13][14][15][16][17] Such multifunctional aptamers exhibit unique optical, electrochemical and magnetic properties, polyvalent interactions, and extraordinary intracellular stability, allowing them to be used as probes, inhibitors or drug delivery systems for target analytes or cells.…”
Section: Introductionmentioning
confidence: 99%
“…TBA-modified AuNPs (TBA–AuNPs) have been prepared previously and employed to detect and control the activity of thrombin. Two well-known TBAs possess 15 (TBA 15 ) and 29 (TBA 29 ) bases that bind to exosite 1 and exosite 2 with dissociation constants ( K d ) of approximately 100 and 0.5 nM, respectively . We have found that TBA 29 –P 8 T 15 –AuNPs (AuNPs conjugated with TBA 15 and TBA 29 ; 15 thymine (T) units in the linker and eight stem pairs (P) at the termini of the TBAs) interact strongly with thrombin, with both reproducibility and repeatability .…”
Section: Results and Disscusionmentioning
confidence: 99%